Clinical Presentation and Outcome of Endoscopic Therapy in Patients with Symptomatic Chronic Pancreatitis Associated with Pancreas Divisum - Bhasin, Deepak Kumar; Rana, Surinder Singh; Sidhu, Rupinder Singh; Nagi, Birinder; Thapa, Babu Ram; Poddar, Ujjal; Gupta, Rajesh; Sinha, Saroj Kant; Singh, Kartar (JOP. Journal of the Pancreas, 2013)
Context The results of endoscopic drainage in pancreas divisum with chronic pancreatitis have been debatable. Objective To evaluate clinical presentation and long term results of endoscopic therapy in patients of calcific and non-calcific chronic pancreatitis with pancreas divisum. Patients and Methods Between 1996 and 2011, 48 patients (32 males and 16 females) with chronic pancreatitis and pancreas divisum were treated endoscopically. Patients were considered to have clinical success if they had resolution of symptoms and did not require surgery. Results All patients presented with abdominal pain and symptoms were present for 36.6±40.5 months. Pseudocyst, diabetes, pancreatic ascites, pancreatic pleural effusion, segmental portal hypertension and steatorrhea were seen in 13 (27.1%), 6 (12.5%), 3 (6.3%), 2 (4.2%), 2 (4.2%) and 1 (2.1%) patients, respectively. Ductal calculi and strictures were noted in 3 (6.3%) and 2 (4.2%) patients, respectively. In 47 patients, an endoprosthesis (5 or 7 Fr) was successfully placed in the dorsal duct. Following pancreatic endotherapy, 45/47 (95.7%) patients had successful outcome. The mean number of stenting sessions required to have clinical success was 2.6±0.9. One patient each had mild post ERCP pancreatitis, inward migration of stent and precipitation of diabetic ketoacidosis. Over a follow up of 2-174 months (median: 67 months), 12 out of 31 patients with pain only and no local complications (38.7%) required restenting for recurrence of pain and none of these patients required surgery. Conclusion Intensive pancreatic endotherapy is safe and effective both in patients with chronic calcific, as well as non-calcific, pancreatitis associated with pancreas divisum. It gives good long term response in patients having abdominal pain and/or dorsal ductal disruptions. Image: Stent placed after minor papillotomy.